History of Medieval India: Exploring the Islamic History in Medieval India (Journal of Advances and Scholarly Researches in Allied Education, 2012)
No wonder, a continuous chronological record of the majorevents of Islamic history in India is available in a series of works rangingfrom the seventh to the nineteenth century, and covering both dynasties andregions. There are a number of authentic historical works on the conquest ofSind by Muhammad bin Qasim and on the invasions of Mahmud of Ghazni andMuhammad Ghauri. With the establishment of Muslim rule in India official andnon-official chroniclers produced works covering all the dynasties of theCentral Sultanate of Delhi (C. 1200-1526) as well as the dynasties of thevarious Muslim kingdoms that arose on the ashes of the Sultanate. Some of thewriters, though religious bigots like Ziyauddin Barani and Abdul Qadir Badaoni,were geniuses in their own way.